PELATIHAN PENGGUNAAN APLIKASI TRELLO PADA KANTOR NOTARIS & PPAT ANINDITA DEA ROSA, S.H., M.KN. DI TANGGERANG SELATAN, BANTEN - Nico Bustanul Anshary; Amaliasyifa Agustina; Agung Ferdinan Sandy; Danu Ega (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Advancements in digital technology have prompted various organizations to adopt more effective and efficient work management systems. One widely used application is Trello, a Kanban-based platform that facilitates task management, team collaboration, and visual progress tracking. However, the Notary & Land Deed Official (PPAT) office of Anindita Dea Rosa, S.H., M.Kn. still manages its work using conventional methods, creating a risk of delays, administrative errors, and suboptimal staff coordination. This Community Service (PkM) initiative aims to enhance the partners' knowledge, skills, and capabilities in utilizing Trello as a digital task management tool. The methodology employed involved participatory training and mentoring conducted in four stages: needs analysis, three online training sessions, an offline training session featuring hands-on practice at the partner's workplace, and an evaluation using pre- and post-training questionnaires. The results indicate that prior to the training, 60% of participants were unfamiliar with Trello, and 80% relied on spreadsheets as their primary tool for work management. Following the training, all participants (100%) expressed interest in using the application. Furthermore, 80% of participants demonstrated improved understanding of Trello's functions—specifically board creation, card management, deadline setting, checklist usage, and team collaboration. Nevertheless, some participants still require further mentoring to fully optimize collaborative features and establish digital-based work habits. Overall, this Community Service activity successfully enhanced the partners' competence in managing tasks more systematically, collaboratively, and efficiently, thereby potentially improving service quality at the Notary & PPAT office.